Oviposition by Plagiodera versicolora on Salix matsudana cv. ‘Zhuliu’ alters the leaf transcriptome and impairs larval performance - Liu, Fengjie; Li, Bin; Liu, Chenghu; Liu, Yipeng; Liu, Xiaolong; Lu, Min (Frontiers in Plant Science, 2023)
Insect egg deposition can induce plant defenses against their larvae. Previous studies have primarily focused on herbaceous plant defense, however, little is known about how the Salicaceae respond to insect egg deposition and defend themselves against herbivores. By combining plant defense gene studies and bioassays, we investigated the effect of the coleoptera Plagiodera versicolora egg deposition on willow (Salix matsudana cv. Zhuliu) and examined the interactions at the plant resistance and transcriptome levels. RNA-seq data was utilized to analyze changes in the leaf transcriptome with and without oviposition, as well as the changes in the feeding-damaged leaves transcriptome with and without prior oviposition. P. versicolora oviposition on willow leaves resulted in altered expression levels of transcripts associated with plant stress and metabolic responses. Compared to no oviposition, leaves with egg deposition showed a slight increase in phenylpropanoid biosynthesis and phytohormone signaling genes after larval feeding. The RNA-seq analysis revealed alterations in willow transcripts in response to leaf beetle infestation. Bioassays indicated that P. versicolora prior oviposition on willows reduced the subsequent larvae performance, suggesting that oviposition by P. versicolora could increase the willow resistance to larvae. This study advances our knowledge of how oviposition by coleoptera insects induces changes in resistance of leaves to herbivory in the Salicaceae family.